2012
DOI: 10.3168/jds.2011-4953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pen size, group size, and stocking density on activity in freestall-housed dairy cows

Abstract: The purpose was to determine the effects of the physical dimensions of the pen and group size and stocking density on cow activity. Cows (randomly assigned to 4 groups of 6 animals each) were tested in pens with 24 or 12 lying places and in groups with 12 or 6 cows. All groups were tested in each of the 4 treatments with treatment order allocated using a 4 × 4 Latin square. The distance moved and the number of movements were calculated using 5-min scan sampling of video recordings over a 48-h period. Time spen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
47
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 24 publications
6
47
2
2
Order By: Relevance
“…Most studies have focused on overstocking (Falk et al, 2012;Fregonesi et al, 2007;Hill et al, 2009;Krawczel et al, 2008Krawczel et al, , 2012. In agreement with the present study, Telezhenko et al (2012) found a similar small increase in lying with understocking. Epidemiological studies, with both under-and overstocked farms included, have often not identified stocking density as an important risk factor for total lying time (Charlton et al, 2014;Ito et al, 2014;Lombard et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Most studies have focused on overstocking (Falk et al, 2012;Fregonesi et al, 2007;Hill et al, 2009;Krawczel et al, 2008Krawczel et al, , 2012. In agreement with the present study, Telezhenko et al (2012) found a similar small increase in lying with understocking. Epidemiological studies, with both under-and overstocked farms included, have often not identified stocking density as an important risk factor for total lying time (Charlton et al, 2014;Ito et al, 2014;Lombard et al, 2010).…”
Section: Discussionsupporting
confidence: 94%
“…Thirty-nine percent of US freestall farms understock (USDA, 2010) and recent research suggests that this practice could increase lying times beyond those seen when 1 stall is offered for every cow (Telezhenko et al, 2012). However, little is known about the other effects of this practice.…”
Section: Introductionmentioning
confidence: 97%
“…Frequency of aggression at the feed trough was not affected by treatment, which may be attributed to allowing each calf an ample feeder space allowance by portioning the trough. Results of the present study agree with those of Telezhenko et al (2012), who found that number of displacements at the feed bunk was not affected by group size (6 vs. 12 calves per group). Kundo et al (1989) reported that sufficient space was of greater importance than group size to reduce the occurrence of agonistic behavior in calves.…”
Section: Effect Of Group Size On Behaviorsupporting
confidence: 92%
“…Faerevik, 2003), or may be attributed to increased usable space in pens of these groups (Chua et al, 2002). Telezhenko et al (2012) found that group size had no effect on movement of cows. They concluded that pen size may be more important than density or group size because group-housed dairy cows were able to share the space in the pen, and even with the same number of cows per square meter, larger pens provided more free space for cows to move about.…”
Section: Effect Of Group Size On Behaviormentioning
confidence: 94%
“…Krawczel et al (2012) reported lying time was reduced for stocking densities of 131 and 142% compared with 100 or 113%. Late-lactation cows stocked at 100% of stalls spent less time lying down compared with cows stocked at 25% of stalls (Telezhenko et al, 2012).…”
Section: Introductionmentioning
confidence: 99%